Impaired Compensatory Vasodilatory Effect Mediated by Wolfram Syndrome 1 and Corticotropin-Releasing Hormone Family Peptides in 17α-Ethynylestradiol-Induced Intrahepatic Cholestasis Pregnant Rats When Under Additional Acute Hypoxia Stress - Tingting Xu; Daijuan Chen; Xixi Deng; Yongchi Zhan; Fan Zhou; Xiaodong Wang; Dandan Shi (Wolters Kluwer Health, 2022)
Abstract. Objective:. To investigate the possible regulatory mechanism of corticotropin-releasing hormone (CRH), urocortin (UCN), and Wolfram syndrome 1 (WFS1) in 17α-ethynylestradiol (EE)-induced intrahepatic cholestasis pregnant rats and its ischemia reperfusion (IR) model. Methods:. Pregnant rats (n = 60) were randomly divided into four experimental groups by random number table (Control, EE, IR, and EE-IR groups), and were studied on the 17th, 19th, and 21st gestational days (GD) (n = 5 in each group at the indicated time). Growth and development indicators of fetal rats among these four groups were recorded. Enzyme-linked immunosorbent assay was employed to detect CRH, UCN, and WFS1 levels in maternal sera. Western blotting and real-time polymerase chain reaction were used to quantify placental protein and placental mRNA levels of CRH, UCN, and WFS1. Multivariate analysis of variance and least significant difference test were used to establish the group and individual comparisons. Results:. A significant difference was found in placenta weight (F = 8.10, P < 0.05), fetal rat weight (F = 40.86, P < 0.05), fetal rat length (F = 61.61, P < 0.05), and fetal rat tail length (F = 55.63, P < 0.05) among four groups on the 17th ,19th , and 21st GD.What's more, the overall differences of maternal serum UCN levels among Control, EE, IR, and EE-IR groups were significant (F = 2.48, P < 0.05). Expression of WFS1 mRNA in the EE-IR group was significantly increased and higher than Control (0.46 ± 0.15 vs. 0.24 ± 0.09, P < 0.05), EE (0.46 ± 0.15 vs. 0.17 ± 0.04, P > 0.05), and IR (0.46 ± 0.15 vs. 0.22 ± 0.15, P > 0.05) groups at 19th GD, indicating that endoplasmic reticulum stress may be activated. However, the expression of CRH (0.42 ± 0.05 vs. 0.58 ± 0.12, P < 0.05), UCN (0.43 ± 0.01 vs. 0.47 ± 0.16, P > 0.05), and WFS1 (0.57 ± 0.07 vs. 0.74 ± 0.12, P > 0.05) protein in the EE-IR group was subsided compared to the IR group at 17th GD. Conclusion:. Fetal rat growth restriction was found in the EE-induced intrahepatic cholestasis model. This study revealed that significant changes in the maternal sera level of UCN , placental level of WFS1 mRNA and placental levels of CRH, UCN, and WFS1 protein in chronic versus acute stress in a rat model of pregnancy. This suggests an impaired compensatory vasodilatory effect mediated by these factors at gene transcription and protein translation levels, following acute hypoxia stress in EE-induced intrahepatic cholestasis in pregnant rats.